An assessment into the bridging the funding gap at Hwange power station: case of Hwange power station (hps) - Ndlovu, Chalila (Midlands State University, 2017)
The researcher was pushed by the need to undertake the study in the energy sector Hwange Power Station in bridging the funding gap. Hwange Power Station being the largest thermal power station in the country with an installed capacity of 1200 megawatt with six units fired by coal and diesel. Conduction of the research was done between the period June 2014 to October 2014.The data was collected from the sample size of 29 who were categorized as follows 6 from the top management, 8 from middle management and 15 from the staff. A descriptive research design was used. The researcher made use of questionnaires and interviews to gather data from respondents. The obtained information was presented in form of tables, graphs and pie charts as guided by the objectives. The findings reflected that the funding policy and the guidelines are not being communicated to employees, the controls are reviewed yearly, the policy are implemented without consultation of the employees, the procurement system is also very weak and no investments are incorporated in trying to bridge the funding gap. Basing on the findings the researcher recommends the organisation to providethe training of employees through workshops and seminarsto educate them so as to work at same wave length with management on the policy. The reviews of the of the controls is suggested to be done quarterly or half yearly so as to adjust and adapt to economic changes and monitor the procurement system which is weak in the organisation. The researcher also suggested that the organisation should also engage local and international players in investments to try and bridge the funding gap at Hwange Power Station.